Outcome Predictor of Spontaneous Supratentorial Intracerebral Hemorrhage Management (Bangladesh Journal of Neurosurgery, 2024)
Background: Spontaneous intracerebral hemorrhage (SICH) is responsible for higher  morbidity and mortality rates than ischemic stroke. Although SICH is less common  than ischemic stroke. Identifying the predictors of outcome after spontaneous  supratentorial intracerebral hemorrhage is crucial for a clinical decision-making  framework and implementing efficient therapeutic measures.  Aims: The study aimed to analyze the clinical profile, assess the outcome, and  identify the outcome prognosticators after supratentorial SICH in the Neurosurgery  Department of a tertiary care hospital in the southeastern part of Bangladesh.  Materials and Methods: This prospective interventional study included 183  patients with computerized tomography (CT) evidence of supratentorial SICH above  18 years of age from the Department of Neurosurgery of Chittagong Medical College  Hospital between September 2021 and February 2023.The variables analyzed were  age, sex, comorbidities, Glasgow coma scale (GCS) score on admission, radiological  features, treatment modality and outcome at 90-day. Glasgow outcome scale (GOS)  score was used to assess the outcome. GOS score 4-5 was considered good outcome  and GOS score 1-3 was considered as poor outcome.  Results: The mean age of the patients was 58.9±14.4 years and 52.5% were male. The  90-day mortality rate was 50.8% and 55.2% patients had poor outcomes. On bivariate  analysis, higher age, comorbid CKD state, low GCS score, higher hematoma volume,  midline shift, hydrocephalus and intraventricular hematoma (IVH) were associated with  poor outcome. Independent predictors of poor outcome included a higher baseline age  (OR: 1.07, 95% CI:1.02-1.11, p=0.002), lower GCS on admission (OR: 0.55, 95% CI: 0.39-  0.76, p